Development of Nearpod Media Assisted with Songs to Improve Learning Outcomes in the Concept of Natural Science on the Material of Force - Kamila, Aisyah Tasya; Sutikno, Putri Yanuarita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The development of science makes using technology-based learning media important to create effective and interesting learning. The use of nearpod media can improve student learning outcomes. This study examines the feasibility and effectiveness of song-assisted nearpod products on force materials. The development model used in this study is ADDIE, which has five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in the study were 28 students in grade IV of elementary school. The research instruments used were interview sheets, observation sheets, questionnaire sheets, and tests. The study results show that the near pod developed is a very feasible product, with a feasibility percentage of 95% from material experts and 94% from media experts. In addition, the results of the questionnaire responses showed a percentage of 96% of teachers and 94% of students, which indicated that the use of near pods was very feasible both in terms of attractive appearance, ease of access, features such as songs and practicum to contribute to the improvement of student learning outcomes as evidenced by the results of pretest and posttest tests. The normality test was carried out using the Shapiro-Wilk analysis technique with a pretest significance value of 0.061 and post-test data with a significance value of 0.113, which showed normal distributed data. The paired sample t-test showed an increase between the pretest and post-test results with a significant value of 0.000 < 0.05. The N-gain test of 0.7919 or 79% carried out is included in the high category. This shows an increase between pretest and posttest results. This means that developing song-assisted nearpod media effectively improves student learning outcomes. The test score results indicate a significant change in science learning outcomes, namely an increase in posttest scores after applying nearpod media in learning compared to the pretest score before the application of nearpod media.